Open access articles receive more citations in hybrid marine ecology journals - Jeff C. Clements (Canadian Science Publishing, 2017)
The accumulation of evidence that open access publishing can increase citation rates highlights one benefit of universal accessibility to scholarly works. However, studies investigating the effect of open access publishing on citations are typically conducted across a wide variety of journals and disciplines, introducing a number of potential issues and limiting their utility for specific disciplines. Here, I used three primary marine ecology journals with an open access option as a "microcosm" of scientific publishing to determine whether or not open access articles received more citations than non-open access articles during the same time frame, controlling for self-citations, article type, and journal impact factor. I also tested for the effects of time since publication and the number of authors. Citations were positively correlated with time since publication and differed across the three journals. In addition, open access articles received significantly more citations than non-open access articles. Self-citations increased with author number and were affected by a complex interaction between open access, journal, and time since publication. This study demonstrates that open access articles receive more citations in hybrid marine ecology journals, although the causal factors driving this trend are unknown.